2012
DOI: 10.1097/dad.0b013e3182562526
|View full text |Cite
|
Sign up to set email alerts
|

Ileostomy-Associated Chronic Papillomatous Dermatitis Showing Nevus Sebaceous–Like Hyperplasia, HPV 16 Infection, and Lymphedema

Abstract: Chronic papillomatous dermatitis (CPD) is a stoma site complication due to chronic irritant contact dermatitis. Papillomatosis can also arise in the setting of human papillomavirus (HPV) infection or chronic lymphedema (elephantiasis). Herein, we report the case of a 57-year-old female who presented with a papillomatous growth surrounding a loop ileostomy suspected to be recurrent ovarian serous carcinoma. Excisional biopsy demonstrated nevus sebaceous (NS)-like organoid hyperplasia with koilocytes overlying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…HPV 16 has been identified in the verrucoid hyperplasia of peristomal chronic papillomatous dermatitis and nevus sebaceus. 24 There was no HPV DNA by polymerase chain reaction in our case, militating against viral pathogenesis.…”
Section: Discussionmentioning
confidence: 89%
“…HPV 16 has been identified in the verrucoid hyperplasia of peristomal chronic papillomatous dermatitis and nevus sebaceus. 24 There was no HPV DNA by polymerase chain reaction in our case, militating against viral pathogenesis.…”
Section: Discussionmentioning
confidence: 89%
“…Specifically, it has been attributed to the alkaline pH of urine mechanical irritation and epidermodysplasia verruciformis Human Papilloma Virus (HPV) types [2]. 9.5% of stoma patients reportedly develop CPD after the stoma has been present for an average of 6.5 years [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic papillomatous dermatitis (CPD), characterized by pseudo verrucous, pseudo‐epitheliomatous, or acanthomatous epidermal hyperplasia, is a complication of the stoma site caused by chronic irritant contact dermatitis. Raghu et al 23 reviewed 58 cases of CPD and reported ESFA or syringofibromatous epidermal changes in four cases. They also reported CPD associated with proliferation of the sebaceous glands, mimicking nevus sebaceous, in their own case 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Raghu et al 23 reviewed 58 cases of CPD and reported ESFA or syringofibromatous epidermal changes in four cases. They also reported CPD associated with proliferation of the sebaceous glands, mimicking nevus sebaceous, in their own case 23 . The presence of CPD indicated that almost all patients had evidence of some degree of edema, fibrosis, and lymphostasis.…”
Section: Discussionmentioning
confidence: 99%